Influence of zeolite on the nitrous oxide emission and efficient use of nutrients in sweet corn - Martínez-Herrera, Claudia; Puentes-Páramo, Yina Jazbleidi; Menjivar-Flores, Juan Carlos (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
This research aimed to determine the influence of zeolite (clinoptilolite) on the emission of nitrous oxide (N2O) and the efficient use of N-P-K nutrients in sweet corn (Zea mays L.) cultures using the 15N isotopic technique, 2.5% in excess. A complete randomized block design with five treatments and four replicates was used; doses of 236, 75 and 192 kg ha-1 were used for N, P and K, respectively, mixed with 0, 70, 140 and 210 kg ha-1 of zeolite. The emission of N2O was estimated with a closed static chamber at 15, 25, 36, 45, 56, 65 and 76 days after sowing the crop. The efficient nutrient use was determined with the agronomic and recovery fertilizer efficiency of N-P-K. N2O flow and nutrient use efficiencies by treatment showed highly significant differences (P≤0.01); the highest N2O flux was found in the control and the lowest was in T4 (210 kg ha-1 zeolite, 236 kg ha-1 nitrogen, 75 kg ha-1 phosphorus P2O5 and 192 kg ha-1 potassium K2O) as contrasted with the greater nutrient use efficiency in T4, except for nitrogen. This showed the contribution of zeolite in the reduction of N2O emissions and in yield increases.